Acid-sensing ion channel 3 is required for agmatine-induced histamine-independent itch in mice - Zhou, Guo-Kun; Xu, Wen-Jing; Lu, Yi; Zhou, Yan; Feng, Chen-Zhang; Zhang, Jiang-Tao; Sun, Shi-Yu; Wang, Ruo-Meng; Liu, Tong; Wu, Bin (Frontiers in Molecular Neuroscience, 2023)
Introduction Itch is a common symptom of many skin and systemic diseases. Identifying novel endogenous itch mediators and the downstream signaling pathways involved will contribute to the development of new strategies for the treatment of chronic itch. In the present study, we adopted behavioral testing, patch clamp recording and metabonomics analysis to investigate the role of agmatine in itch and the underlying mechanism. Methods Behavioral analysis was used to evaluate the establishing of acute and chronic itch mice model, and to test the effects of different drugs or agents on mice itch behavior. Western blotting analysis was used to test the effect of agmatine on phosphorylation of ERK (p-ERK) expression in the spinal cord. Patch clamp recording was used to determine the effect agmatine on the excitability of DRG neurons and the role of ASIC3. Finally, the metabonomics analysis was performed to detect the concentration of agmatine in the affected skin under atopic dermatitis or psoriasis conditions. Results We fused a mouse model and found that an intradermal injection of agmatine (an endogenous polyamine) into the nape of the neck or cheek induced histamine-independent scratching behavior in a dose-dependent manner. In addition, the ablation of nociceptive C-fibers by resiniferatoxin (RTX) abolished agmatine-induced scratching behavior. However, agmatine-induced itch was not affected by the pharmacological inhibition of either transient receptor potential vanilloid 1 (TRPV1) or transient receptor potential ankyrin 1 (TRPA1); similar results were obtained from TRPV1−/− or TRPA1−/− mice. Furthermore, agmatine-induced itch was significantly suppressed by the administration of acid-sensing ion channel 3 (ASIC3) inhibitors, APETx2 or amiloride. Agmatine also induced the upregulation of p-ERK in the spinal cord; this effect was inhibited by amiloride. Current clamp recording showed that the acute perfusion of agmatine reduced the rheobase and increased the number of evoked action potentials in acute dissociated dorsal root ganglion (DRG) neurons while amiloride reversed agmatine-induced neuronal hyperexcitability. Finally, we identified significantly higher levels of agmatine in the affected skin of a mouse model of atopic dermatitis (AD) when compared to controls, and the scratching behavior of AD mice was significantly attenuated by blocking ASIC3. Discussion Collectively, these results provide evidence that agmatine is a novel mediator of itch and induces itch via the activation of ASIC3. Targeting neuronal ASIC3 signaling may represent a novel strategy for the treatment of itch.